Where Will We Draw the Line? Public Opinions of Human Gene Editing. (October 2019) - Riggan, Kirsten A.; Sharp, Richard R.; Allyse, Megan
The application of gene editing technologies to prevent or mitigate genetic disease in humans is considered one of its most promising applications. However, as the technology advances, it is imperative to understand the views of the broader public on how it should be used. We conducted focus groups to understand public views on the ethical permissibility and governance of gene editing technologies in humans. A total of 50 urban and semirural residents in the upper Midwest took part in six focus groups. Participants expressed multiple concerns about nonmedical uses of gene editing and its potential for unknown harms to human health, and were divided as to whether the individual patient or "medical experts" should be charged with overseeing the scope of its application. As potential stakeholders, the perspectives from the general public are critical to assess as genome editing technologies advance toward the clinic.